DETERMINE HOUSING NEED IN BURAIDAH CITY – SAUDI ARABIA A CASE STUDY IN URBAN PLANNING GEOGRAPHY - Al-Madhian, Areej Ali (Journal of natural sciences, life and applied sciences, 2020)
This study aimed to state factors which caused increase of housing necessity in Buraidah city and the mass of this necessity, using a survey method, the study unleashed the factors that’s caused the increase of housing need in Buraidah city to be considered. using a quantitative method study by Appling a group of math’s equations to determine housing need, this study based on two pillars: - factors that led to increase of housing need. - state housing need. The study resulted of a group of points: Increase of housing demand in Buraidah city caused by many factors: related to people, housing, some housing polices. The study highlighted on immigration into Buraidah city is one of most factors the led to housing demand, as well as the role of some housing polices in Buraidah city. In the year 1438 a total of (100465) houses, the study estimated housing need in Buraidah city as a result of people increase. Increase in marriage rates in Buraidah city estimated the of houses in the year 1438 by (11634) houses ,as the study resulted that cause of housing need to reduce crowd in Buraidah city in the year 1438 a total sum of (48783) house is needed. The study recommended an emphasized on the importance of development of rural areas to stop immigration to the cities, find more finance funding, renew all old and random houses.